Conference on the North Sea floods of 31 January/1 February, 1953 a collection of papers presented at the Institution in December 1953. (Institution of Civil Engineers, 1954)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in December 1953.